Checklist and plant communities of Cerro Giubldan, San Bartolomé Quialana, Oaxaca, Mexico - Aragón-Parada, Juvenal; García-Mendoza, Abisaí Josué; González-Adame, Gabriel (Instituto de Ecología, A.C., 2021)
Background and Aims: Oaxaca, with more than 9362 species of vascular plants and 26 vegetation types, is the state with the greatest floristic diversity in Mexico. However, the diversity of large areas of its territory is still unknown. The Giubldan hill is located in the municipality of San Bartolomé Quialana, Tlacolula District, in the Valles Centrales region of the state, and does not have any study that refers to its flora and vegetation. This study aims to present the floristic inventory of Cerro Giubldan, and identify the families and genera with greater and lesser representation, describe the plant communities present and the area they occupy. Methods: From 2012 to 2015, field trips were carried out to collect plants with reproductive structures, which were processed and later deposited in the herbaria HUNSIJ, IBUG, IEB, and MEXU. The specimens were identified with specialized keys, help of specialists, and compared with MEXU herbarium material and the REMIB database. Key results: The vascular flora comprised 100 families, 308 genera and 535 species. The most diverse families were Asteraceae (81), Fabaceae (47), Orchidaceae (30), Lamiaceae (18), Asparagaceae (15), and Crassulaceae (15). The richest genera were Salvia (14), Quercus (9), Agave (7), Echeveria (7), Solanum (7), and Lamourouxia (6). One hundred and sixty seven species are reported as endemic to Mexico and 43 are endemic to Oaxaca, eight represent new records at the species level for the state. Four plant communities were described and characterized: Quercus deciduous forest, Quercus evergreen forest, xerophilous scrub, and rupicolous community. Conclusions: The greatest richness of plant species was concentrated in 15 families represented by herbs, shrubs, and trees. The deciduous Quercus forest presented the highest diversity, followed by the evergreen Quercus forest and the xerophilous scrub.